2022
DOI: 10.1007/s11409-022-09306-x
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal associations between executive functions and metacognitive monitoring in 5- to 8-year-olds

Abstract: Pronounced developmental progression during the transition to formal schooling can be found in executive functions (EF) and metacognition (MC). However, it is still unclear whether and how EF and MC influence each other during this transition. Previous research with young children suggests that inhibition may be a prerequisite for monitoring skills. Thus, the present longitudinal study investigated the association between the common subcomponents of EF (inhibition, working memory, and shifting) assessed in kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…The first longitudinal study of these skillsets found some evidence to suggest that performance in an inhibitory control task at 7 years was predictive of metacognitive control (as measured by the ability to withdraw incorrectly spelt words in a spelling test) at age 8 years (Roebers et al, 2012). Moreover, a recent longitudinal study following the development of 5-to 6-year-old children replicated this result for metacognitive monitoring, finding that children's performance on an inhibitory control task was predictive of their ability to accurately report their level of certainty during a recall task one year later (Kälin & Roebers, 2022). Thus, it is possible that self-control is involved in the development of children's ability to take a metarepresentational stance on their own thoughts.…”
Section: Theory Of Mind Metacognition and Self-controlmentioning
confidence: 78%
See 2 more Smart Citations
“…The first longitudinal study of these skillsets found some evidence to suggest that performance in an inhibitory control task at 7 years was predictive of metacognitive control (as measured by the ability to withdraw incorrectly spelt words in a spelling test) at age 8 years (Roebers et al, 2012). Moreover, a recent longitudinal study following the development of 5-to 6-year-old children replicated this result for metacognitive monitoring, finding that children's performance on an inhibitory control task was predictive of their ability to accurately report their level of certainty during a recall task one year later (Kälin & Roebers, 2022). Thus, it is possible that self-control is involved in the development of children's ability to take a metarepresentational stance on their own thoughts.…”
Section: Theory Of Mind Metacognition and Self-controlmentioning
confidence: 78%
“…As set out above, self-control might be thought of as a higher order form of metacognition (see Roebers, 2017 for review). This definitional overlap, together with a lack of longitudinal evidence, makes it difficult to unpick the developmental trajectories of metacognitive monitoring and self-control (Kälin & Roebers, 2022). The first longitudinal study of these skillsets found some evidence to suggest that performance in an inhibitory control task at 7 years was predictive of metacognitive control (as measured by the ability to withdraw incorrectly spelt words in a spelling test) at age 8 years (Roebers et al, 2012).…”
Section: Theory Of Mind Metacognition and Self-controlmentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting to note that metacognition and inhibitory control were robustly related in both Japan and Scotland, suggesting that some cognitive control may be required to take a metacognitive stance, as previously argued for western samples (Kälin & Roebers, 2022). However, Zhao et al, (2021) suggest that whereas children from the independent cultures may attribute their ability to control themselves to internal factors such as the ability to inhibit desires, children from interdependent cultures associate inhibitory control with complying to external rules, without reflection of their own willpower.…”
Section: Discussionmentioning
confidence: 57%
“…Several frameworks tightly link metacognition and EF at the conceptual level (Bryce et al, 2015; Kälin & Roebers, 2022; Roebers, 2017; Roebers & Feurer, 2016). For instance, age-related gains in monitoring and/or self-reflection abilities have been proposed to drive the development of both metacognition and EF (e.g., Lyons & Zelazo, 2011; Roebers, 2017).…”
mentioning
confidence: 99%